Predictors of Antiviral Therapy in a Post-Transfusion Cohort of Hepatitis C Patients - Maciej Witkos; Qi-Long Yi; Jenny Heathcote; Moira K Kapral; Murray D Krahn (Canadian Journal of Gastroenterology)
INTRODUCTION: In the past, antiviral therapy has been given to 15% to 30% of patients infected with hepatitis C virus (HCV). The efficacy of therapy has recently improved with the addition of ribavirin and pegylated interferon. The aim of the present study was to identify the clinical, socioeconomic and health-system predictors of antiviral treatment for HCV.